Applying SOFL to construct requirements specification for examination monitoring system - Abdul Rahman, Mat; M.A., Khairuddin; Azman Bujang, Masli; Mohamad Nazim, Jambli; Edwin, Mit (IEEE, 2012)
SOFL approach to the construction of the formal specifications has been proposed and applied in information systems, but its effectiveness and applicability have not been demonstrated aggressively. In this paper, we describe an application of the SOFL approach to the construction of a specification during requirements analysis. This approach requires two steps: informal and semi-formal steps. In order to describe on how this approach can be applied to capture requirements using SOFL easily, we use a case study to develop an examination monitoring system for construct abstract requirements. This case study demonstrates the suitability of SOFL to capture detail requirements and provides us with an insight into the knowledge of how SOFL approach can be effectively supported.